"Jimmy Cap Before You Tap": Developing Condom Use Messages for African American Women. Issue 4 (13th June 2017) - Hood, Kristina B.; Shook, Natalie J.; Belgrave, Faye Z.
Abstract : This study examined which characteristics of persuasive communications are most effective in changing African American women's condom use attitudes. Focus groups were convened with 40 African American women (Mage  = 25.54, SD = 4.67) to assess their opinions on current effective strategies used to promote condom use among their peers. Participants discussed effective characteristics of messaging campaigns (i.e., source, message type, channel) and how these could be used in future prevention messages. Findings revealed that making messages that are fun, catchy, and informative, delivered frequently through social media, TV, or radio by a peer or celebrity would be perceived as most effective in changing young African American women's attitudes. Other themes that emerged were that condom use is more strongly associated with pregnancy prevention than HIV prevention and that sexual partners were perceived to have negative condom use attitudes. Recommendations centered on increasing exposure of HIV prevention messages by placing messages on the Internet and including a funny phrase or jingle in the message so that it is easy to remember and could potentially serve as a conversation starter for discussing safe sex with partners.